The Literacies Effectiveness of Short Story Writing Learning Model - Sitti Rachmie Masie; Wahyudi Siswanto; Yuni Pratiwi; Heri Suwignyo (Journal of Language Teaching and Research, 2023)
This research method was a development research employing Borg and Gall (R & D) model which aims at developing short story writing learning material. The research steps were: (1) conducting a preliminary study or research to find the research findings related to the product, (2) developing the product based on the preliminary study, (3) conducting the field test, and (4) revising the product to improve the weaknesses found during field trials. The results of the study showed that first, the quality of short story writing learning requires creative strategies to achieve learning objectives. Second, the results of text-writing learning model assessment using conversion text encompassing entrepreneurial values obtained a positive score from the expert test, practitioner test, small field test, and extensive field test. Third, the learning model of short story writing with text conversion strategy encompassing entrepreneurial values can significantly improve the ability of students to write short stories compared to conventional models.